Photoelectric photometry of algol and Hamal stars / Nazirah Mohd Noris. - Mohd Noris, Nazirah (2010)
Photoelectric Photometry is technique of astronomy concerned with measuring flux, the most fundamental and oldest research technique and gives information about the total energy emitted by the object, its size, its temperature and other physical properties. Algol star is variable star that changes the brightness of the star. From the surface temperature range 10,000K until 28,000K is B spectral class, appear more bluish colour and have light curve. The comparison star is Hamal star is non- variable star that not changes brightness of the star. Hamal has the surface temperature range from 3500K to 4900K so it can classified in K spectral and the colour index (B-V) is positive value, so the star appear reddish colour.